The association between adiponectin level and non alcoholic fatty liver disease (NAFLD) in obese adolescents - Mexitalia, Maria; Romadhona, Suci (RSUP Dr. Kariadi, 2020)
Background: Non alcoholic fatty liver disease (NAFLD) has been associated with cytokines and inflammatory mediators. Adiponectin has insulin sensitizing effects and has correlation with severity of NAFLD disease. However, the study about the relationship between adiponectin level and NAFLD is lacking. The objective of the study was to determine the association between adiponectin level and NAFLD in obese adolescents through the role of insulin resistance. Methods: This was a cross-sectional study, that was done in August 2007. The inclusion criteria were obese adolescents aged 11-14 years, and normal weight adolescent as control group. Adiponectin was assessed by using ELISA, insulin resistance was obtained by Homeostasis Model Assessment Insulin Resistance (HOMA-IR). NAFLD was confirmed by abdominal ultrasound, which represented by fatty liver imaging. The comparison of adiponectin level and HOMA-IR among 3 groups were analyzed by Kruskal Wallis test, meanwhile the correlation between adiponectin level and some variables were analyzed by spearman correlation. Result: There were 73 subjects, consisted of 37 obese and 36 non obese. Among obese subjects, 54.1% got NAFLD. All of our obese subjects were insulin resistance, the HOMA-IR level of obese non NAFLD was 6.1 and obese with NAFLD was 6.8. The adiponectin levels in normal children was (5.1mg / ml), obese non NAFLD (4.1mg / ml) and obese with NAFLD (4.0 mg / ml) (p <0.001). There were no association between adiponectin level and other variables. Conclusion: There were significant differences of adiponectin levels and insulin resistance measured by HOMA-IR between normal and obese subjects, but no significant differences between the obese groups with or without NAFLD. Keywords: NAFLD, adiponectin, HOMA-IR, obesity, adolescent.